Effects of Strain and Production-Cycle on Indices of Lysine Catabolism in Turkeys - Gatrell, S.K.; Swiger, B.N.; Engels, J.G.; Berg, L.E.; Barnard, J.T.; Mortiz, J.S.; Blemings , K.P. (International Journal of Poultry Science, 2014)
In typical turkey production diets, lysine is frequently the second limiting amino acid. Understanding its catabolism could provide opportunities to increase the efficiency of lysine use for protein synthesis. We hypothesize that indices of lysine catabolism in turkey liver vary throughout the production cycle. Two commercial strains of turkey, Strain A and B, were analyzed 8 times over a period of 17 weeks (n = 8 birds/sampling time/strain) for lysine alpha-ketoglutarate (LKR) and saccharopine dehydrogenase (SDH) activities and mRNA abundance, in vitro lysine oxidation (LOX), L-amino acid oxidase (LAAO) activity, lysyl oxidase (LO) activity and mRNA expression of cationic amino acid transporters (CAT) 1, 2 and 3. We found differences in hepatic LKR activity (p = 0.007), LKR mRNA (p = 0.0004), SDH activity (p = 0.008), LOX (p<0.0001), lysyl oxidase activity (p<0.01), LAAO (p<0.0001) and CAT1 (p = 0.005) and 2 mRNA abundance (p = 0.0022) throughout the production cycle. We also found an effect of strain on SDH (p = 0.046) and CAT-2 mRNA abundance (p = 0.02); while no age or strain effects were detected for CAT3 mRNA abundance. Interestingly, the average LKR and SDH activities across strains and weeks was 240 and 420 nmol per minute per gram of liver, respectively, as opposed to the average LAAO activity, lysyl oxidase activity and L OX which were 0.70, 0.10 and 13.5 nmol per minute per gram liver, respectively. These data indicate that the saccharopine-dependent pathway is the predominant pathway of lysine degradation in turkey liver and that indices of hepatic lysine catabolism vary throughout the production cycle.